ℋ∞ Control Tunning to Guarantee the Output Performance of LTI Second-Order Systems. Issue 2 (2020) - Verdés, Ramón I.; Aguilar, Luis T.; Orlov, Yury
Abstract: Settling time and input/output specifications are general for optimal operation of control systems and for their avoiding irreversible damages. We present an ℋ∞ control design whose parameters are tuned, not only to achieve the robustness property but also to meet the step time response characteristic of a linear time-invariant second-order system. We present explicit formulas in terms of the settling time and overshoot response. Simulation and experimental evidence corroborate the results.